Long-term metabolic cage housing increases anxiety/depression-related behaviours in adult male rats - Sahin, Zafer; Solak, Hatice; Koc, Aynur; Koca, Raviye Ozen; Ozkurkculer, Alpaslan; Cakan, Pinar; Kelestimur, Haluk (Taylor & Francis Ltd, 2019)
There are several reports on unfavourable effects of metabolic cage housing on animal welfare mainly due to the characteristic structures of these cages such as single housing and grid flooring. This study was aimed to compare the effects of long-term metabolic cage housing and conventional housing (normal grouped housing in standard cages) on the anxiety/depression-like behaviours in male rats. Anxiety/depression-related behaviours were evaluated by use of forced swimming test and open field test. Swimming and climbing were significantly lower and immobility duration higher in the metabolic cage group. In the open field test, total distance, mean velocity, time spent in the central area, zone transition, grooming, and rearing scores were significantly lower in the metabolic cage. Moreover, serum corticosterone level was higher in the metabolic cage group. The results of the study indicate that long-term metabolic cage housing may cause an increase in the anxiety- and depression-related behaviours in male rats.
Keywords: Metabolic cage; corticosterone; stress; anxiety; depression